From Flood Risk to Caloric Loss: Compound Flood Impacts on Agriculture in Madagascar - Thomé, Celina; Schauß, Anne; Maurer, Marcel; Lautenbach, Sven; Zipf, Alexander; Grinblat, Yulia (Proceedings of the International ISCRAM Conference, 2026)
Flood hazards increasingly threaten food production in Madagascar, yet spatially explicit assessments that translate flood exposure into nutritionally meaningful impacts remain limited. This study develops a spatially explicit framework that combines nationwide crop type mapping, compound flood hazard scenarios, and depth-dependent crop damage functions to estimate flood-induced caloric losses under baseline conditions (2020) and future climate pathways (2030, 2050, and 2080; SSP1, SSP2, SSP3, and SSP5). A custom crop classification model achieved 72% overall accuracy and enabled mapping of key staple crop groups across Madagascar. Potential caloric production was then estimated and combined with compound flood depth maps to derive crop-specific relative losses, district-level spatial impact patterns, and national absolute caloric loss trajectories. Under the 2020 baseline flood scenario, estimated caloric losses translate to people not being fed, equivalent to the annual minimum dietary energy requirement of about 3.3 million people in a 1-in-5-year event and more than 9 million people in a 1-in-100-year event, with impacts increasing for rarer floods and intensifying under high-emission futures. By shifting the proxy from flooded area to human-centred indicators (calories and people-equivalents), the framework provides decision-relevant evidence for preparedness planning, anticipatory action, and humanitarian prioritisation.